Research Progress on Main Symptoms of Novel Coronavirus Pneumonia Improved by Traditional Chinese Medicine - Luo, Chuan-hong; Ma, Le-le; Liu, Hui-min; Liao, Wei; Xu, Run-chun; Ci, Zhi-min; Lin, Jun-zhi; Han, Li; Zhang, Ding-kun (Frontiers in Pharmacology, 2020)
The nNovel coronavirus pneumonia (COVID-19) pneumonia has become a major threat to worldwide global public health, having rapidly spread to more than 180 countries have been rapidly spread and infecting over 1.6 billion peoplenearly 2 million people were infected. Fever, cough, and fatigue are the most common initialearly symptoms of COVID-19, while some special patients experienceshow diarrhea rather than fever in the early stage. Many herbal medicine and Chinese patent medicine can significantly improve these symptoms, cure the patients experiencing a mild form of thewith mild illness, reduce the rate of transitiontransfer from mild to severe disease, and reduce mortality. Therefore, this paper summarizesd the physiopathological mechanisms of fever, cough, fatigue and diarrhea, and introducesd Chinese herbal medicines (Ephedrae Herba, Gypsum Fibrosum, Glycyrrhizae Radix et Rhizoma, Asteris Radix et Rhizoma, Ginseng Radix et Rhizoma, Codonopsis Radix, Atractylodis Rhizoma, etc.) and Chinese patent medicines (Shuang-huang-lian, Ma-xing-gan-shi-tang, etc.) with their corresponding therapeutic effects. Emphasis was placed on their material basis, mechanism of action, and clinical research. Most of these medicines possess the pharmacological activities of anti-inflammatory, antioxidant, antiviral, and immunitye-enhancementing, and may be promising medicines for the treatment or adjuvant treatment of COVID-19 patients.